하지 골절을 동반한 중증 외상 환자에 있어서 정맥혈전색전증의 빈도 및 예방 - 김지완(Ji Wan Kim); 최지호(Ji Ho Choi); 김정재(Jung Jae Kim,) (The journal of the Korean Orthopaedic Association, 2012)
목적: 하지 골절을 동반한 중증 외상 환자에서 발생하는 정맥혈전색전증의 빈도를 확인하고, 예방법을 시행한 후 그 빈도의 차이를 후향적 연구를 통해 알아보고자 하였다. 대상 및 방법: 항응고제 및 물리적인 예방법 시행 이전을 1기, 시행 이후를 2기로 나누어 두 군에서의 정맥혈전색전증 빈도에 대해 조사하였다. 결과: 1기에서 대상 31예 중 5예(16.1%)에서 임상적 증상이 있는 정맥혈전색전증이 발생하였는데, 심부정맥혈전증이 1예, 폐색전증이 4예였고, 그 중 2예는 생명을 위협할 정도의 중증의 폐색전증을 보였다. 2기에서 대상 환자는 32예였고, 이 중 임상적 증상이 있는 정맥혈전색전증은 1예도 없었다. 결론: 중증 외상 환자에서 정맥혈전색전증에 대한 적극적인 예방 조치를 하지 않았을 경우 임상적으로 나타나는 정맥혈전색전증이 16.1%에서 나타났으며. 이는 항응고제 및 물리적인 방법을 통해 현저히 감소하는 것을 확인할 수 있었다. 따라서 중증 외상 환자에서는 정맥혈전색전증에 대한 적극적인 예방이 필요하다 할 것이다. Purpose: To compare the incidence of venous thromboembolism (VTE) in severely injured patients with lower extremity fracture in a prophylactic group with that in a non-prophylactic group during a retrospective study. Materials and Methods: Severely injured patients with lower extremity fracture were enrolled in this study and were divided into the following two groups: Group I, non-prophylactic group, and Group II, prophylactic group using anticoagulants and mechanical prophylaxis. Results: Symptomatic VTE occurred in 5 cases (16.1%) among the 31 cases in Group I; i.e., deep vein thrombosis in one case and pulmonary embolism (PE) in four cases, including life threatening PE 2 cases. There were no patients with symptomatic VTE among the 32 cases in Group II. Conclusion: The incidence of symptomatic VTE without the use of prophylaxis was 16.1%. This rate dramatically decreased with the use of prophylaxis. Therefore, we believe that prophylaxis with anticoagulants and mechanical device is necessary in order to prevent VTE in severely injured patients with lower extremity fracture. KCI Citation Count: 0